Cho a,b,c là 3 số đôi một khác nhau thỏa mãn : `a/(b-c)+ b/(c-a) + c/(a-b) =0` a, CMR: ` a/(b-c)^2 = (b^2-c^2+ ac- ab)/((a-b)(b-c)(c-a))` b,CMR: `a/(b

Cho a,b,c là 3 số đôi một khác nhau thỏa mãn : `a/(b-c)+ b/(c-a) + c/(a-b) =0`
a, CMR: ` a/(b-c)^2 = (b^2-c^2+ ac- ab)/((a-b)(b-c)(c-a))`
b,CMR: `a/(b-c)^2 + b/(c-a)^2 + c/(a-b)^2 = 0`

0 bình luận về “Cho a,b,c là 3 số đôi một khác nhau thỏa mãn : `a/(b-c)+ b/(c-a) + c/(a-b) =0` a, CMR: ` a/(b-c)^2 = (b^2-c^2+ ac- ab)/((a-b)(b-c)(c-a))` b,CMR: `a/(b”

  1. `a/(b-c)+b/(c-a)+c/(a-b)=0`

    `⇔a/(b-c)=-b/(c-a)-c/(a-b)`

    `⇔a/(b-c)=(b^2-ab-c^2+ac)/((c-a)(a-b))`

    `⇔a/((b-c)^2)=(b^2-ab-c^2+ac)/((c-a)(a-b)(b-c))(ĐPCM)`

    tương tự 

    `⇒b/((c-a)^2)=(c^2-cb-a^2+ab)/((c-a)(a-b)(b-c))`

    `⇒c/((a-b)^2)=(a^2-ca-b^2+cb)/((c-a)(a-b)(b-c))`

    `⇒a/((b-c)^2)+b/((c-a)^2)+c/((a-b)^2)=(b^2-ab-c^2+ac)/((c-a)(a-b)(b-c))+(c^2-cb-a^2+ab)/((c-a)(a-b)(b-c))+(a^2-ca-b^2+cb)/((c-a)(a-b)(b-c))=0(ĐPCM)`

    Bình luận

Viết một bình luận